2019
DOI: 10.1111/apm.12929
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Methicillin‐resistant Staphylococcus aureus in a Hospital Center for Children's and Women's Health in a Swedish County

Abstract: The objective of this study was to investigate a sudden increase in methicillin-resistant Staphylococcus aureus (MRSA) cases primarily in one maternity ward at the Center for Children's and Women's Health at Link€ oping University Hospital, Sweden. Approximately 300 individuals including patients, their family members, and healthcare workers were screened for MRSA. The antibiotic susceptibility was tested and isolates polymerase chain reaction (PCR)-positive for the mecA gene were spa typed. Isolates with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Furthermore, it is concerning that these MRSA spa -types have been reported to cause relatively large neonatal outbreaks, in Norway (unpublished data) and in Denmark [ 27 , 30 ]. MRSA t127, along with MRSA t688, was significantly associated with neonates and infants (< 1 year) in this study, the latter also to outbreaks, and has previously been found in maternity wards in Sweden [ 31 ], Ireland [ 32 ] and Kuwait [ 33 ].…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, it is concerning that these MRSA spa -types have been reported to cause relatively large neonatal outbreaks, in Norway (unpublished data) and in Denmark [ 27 , 30 ]. MRSA t127, along with MRSA t688, was significantly associated with neonates and infants (< 1 year) in this study, the latter also to outbreaks, and has previously been found in maternity wards in Sweden [ 31 ], Ireland [ 32 ] and Kuwait [ 33 ].…”
Section: Discussionsupporting
confidence: 73%
“…The most recent data for 85 WHO member countries reported rates exceeding 20% in all regions and even 80% in some countries [28]. MRSA has caused several hospital outbreaks in neonatal care units [29][30][31]. Reports from various studies have discussed the important risk factor of colonized caregivers in the occurrence of these outbreaks [32][33].…”
Section: Discussionmentioning
confidence: 99%
“…5 Although both MSSA and MRSA have been shown to cause outbreaks in NICUs, the focus has mainly been on MRSA outbreaks reported in various NICUs, with several risk factors investigated. 1,2,[6][7][8][9][10][11][12][13] Methicillin-resistant S. aureus may be transmitted directly from asymptomatic carriers (eg parents and health care professionals (HCPs)) or indirectly by contact with contaminated objects or environmental surfaces, where it can survive on dry surfaces for months. [14][15][16] Close contact between admitted neonates and HCPs, parents, and the environment facilitates bacterial flora exchange and colonization, with a subsequent risk of infection.…”
Section: Introductionmentioning
confidence: 99%